PERAN DUKUNGAN ATASAN TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL MELALUI MEDIASI CAREER PLATEAU (Studi pada Pegawai Kantor Kecamatan dan UPT di Lingkungan Kecamatan Kaliori Kabupaten Rembang). (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to identify and examine the role of supervisor support on job satisfaction and organizational commitment through media career plateau by taking an object at the District Office and the Environment Unit in the District Kaliori Rembang. Sampling with purposive sampling technique . From the results of the sample used purposive sampling for this study amounted to 81 people. The test instrument used in the study include test validity by factor analysis and reliability tests with Cronbach alpha formula . Test models using the coefficient of determination and F test to test the hypothesis of linear regression analysis and t test. The results showed that supervisor support does not affect the career plateau. Supervisor support positive and significant effect on job satisfaction and organizational commitment of employees. Career plateau does not affect the employee job satisfaction. Career plateau and a significant negative effect on the organizational commitment of employees. And job satisfaction and a significant positive effect on the organizational commitment of employees of the District Office and the Environment Unit in the District Kaliori Rembang . Keywords :     Supervisor Support, Plateau Career, Job Satisfaction and Organizational Commitment.